The effects of a short specific versus a long traditional warm-up on time-trial performance in cross-country skiing sprint - Strøm Solli, G.; Haugnes, P.; Kocbach, J.; van den Tillaar, R.; Øyvind Torvik, P.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To compare the effects of a short specific and a long traditional warm-up on time-trial performance in cross-country skiing sprint using the skating style, as well as related differences in pacing strategy and physiological responses. Methods: In total, 14 (8 men and 6 women) national-level Norwegian cross-country skiers (age 20.4 [3.1] y; VO2max 65.9 [5.7] mL/kg/min) performed 2 types of warm-up (short, 8×100 m with gradual increase from 60% to 95% of maximal speed with a 1-min rest between sprints, and long, ~35 min at low intensity, including 5 min at moderate and 3 min at high intensity) in a randomized order with 1 hour and 40 minutes of rest between tests. Each warm-up was followed by a 1.3-km sprint time trial, with continuous measurements of speed and heart rate. Results: No difference in total time for the time trial between the short and long warm-ups (199 [17] vs 200 [16] s; P=.952), or average speed and heart rate for the total course, or in the 6 terrain sections (all P<41, eta2<.06) was found. There was an effect of order, with total time-trial time being shorter during test 2 than test 1 (197 [16] vs 202 [16] s; P=.004). No significant difference in blood lactate and rating of perceived exertion was found between the short versus long warm-ups or between test 1 and test 2 at any of the measurement points during the test day (P<.58, eta2>.01). Conclusions: This study indicates that a short specific warm-up could be as effective as a long traditional warm-up during a sprint time trial in cross-country skiing.